The effects of platelet rich plasma on healing of full thickness burns in swine. Issue 6 (September 2018) - Singer, Adam J.; Toussaint, Jimmy; Chung, Won Taek; McClain, Steve; Raut, Vivek; Rosenberg, Lior
Highlights: Platelet rich plasma (PRP) contains multiple wound mediators. We determined if PRP would improve healing when added to tangential excision and grafting in full thickness porcine burns. The effects of PRP on reepithelialization and scarring were similar to standard topical antibiotics. Early excision and grafting sped reepithelialization and reduced scarring. Addition of PRP to excision and grafting did not further speed reepithelialization or reduce scarring. Abstract: Introduction: Platelet rich plasma (PRP) is rich in growth factors and has been shown to improve healing in a variety of wounds. We determined the effects of PRP on healing and scarring in full thickness porcine burns with and without tangential excision and grafting (TEG). Methods: Standardized full thickness 5 cm by 5 cm burns were created on each of the backs and flanks of 10 anesthetized female pigs (25 kg) using a validated model. The burns were created with a heating device that emits heat at a temperature of 400 °C for a period of 30 s. The burns were randomized to one of six treatments: no TEG or PRP, no TEG + PRP, early (day 2) TEG and no PRP, early TEG + PRP, late (day 14) TEG and no PRP, and late TEG + PRP. Tangential excision was performed down to viable tissue and autografts were 0.2 mm thick. When used, a thin layer of autologous PRP was applied below the graft. All wounds were then treated with a topical antibiotic ointment 3 times weekly for 42 days. Digital images and full thickness biopsies were taken at 9, 11, 14, 18, 21, 28, 35 and 42 days after injury to determine percentage reepithelialization, scar depth, and scar contraction. Tissue sections were stained with H&E and viewed by a dermatopathologist masked to treatment assignment. Results: There was no reduction in platelet and white blood cell concentrations in PRP and blood samples for the first 14 days after-full thickness burns. A total of 120 burns were created on 10 animals evenly distributed between the six treatment groups. Burns undergoing early TEG reepithelialized fastest and with the thinnest scars followed by late TEG. Burns that did not undergo TEG had the slowest reepithelialization and greatest amount of scarring. Application of PRP had no additional effects on reepithelialization, scar depth, or scar contraction in any of the treatment groups. Conclusions: Addition of PRP had similar effects on reepithelialization and scarring of full thickness porcine burns as standard topical antibiotic ointment regardless of whether the burns underwent excision or grafting or the timing of excision and grafting.